Approaches to improve the cultural capabilities of teachers engaging with culturally and linguistically diverse students and their families: a scoping review - Bobongie-Harris, Francis; Youse, Zia (Frontiers in Education, 2023)
This scoping review is one part of a research project funded by the Queensland Government Department of Education through their 2021 Horizon Grant funding scheme. This scoping review provides an analysis of contemporary literature that identifies approaches currently being used by educators to successfully engage with culturally and linguistically diverse students, families, and their communities to increase cultural capabilities. A systemic selection process delivered 21 articles that were included in this Scoping Review. The study highlights four common areas educators can focus on to improve their cultural capabilities: (i) eldership; (ii) connections; (iii) relationships; (iv) practice. The discussion draws on these four areas and provides an in-depth summary of the literature presented in the scoping review. The literature from this scoping review will inform an engagement strategy that will help improve upon the cultural capabilities of educators working with students in Australian South Sea Islander Communities.